VESICO-VAGINAL FISTULA: INTERPOSITION FLAP, A KEY TO SUCCESS - Mehmood, Arshad; Alvi, M Sarwar; Rana, Shahid; Raziq, Sohail; Siddiq, Lubna; Shah, M Yousaf (Journal of Ayub Medical College Abbottabad, 2009)
Background: Vesico-vaginal Fistula (VVF) is an abnormal communication between bladder and vagina that causes continuous discharge of urine in to vaginal vault. The objective of this study is to describe current trends of aetiology and repair of Vesico-vaginal Fistulae. This is a Descriptive Study, conducted at Armed Forces Institute of Urology, Rawalpindi and Combined Military Hospital, Kharian between May 2001 and May 2007. Methods: All patients diagnosed as cases of vesico-vaginal fistulae were included in the study. Their demographic profile and repair success was determined. Results: A total of 86 patients were included in the study. The mean age of the patients was 35.5 years (range 25-46). Total abdominal hysterectomy was the most common cause (53% of the cases) followed by obstetric causes (43.92% of the cases). Success rate of the surgery in the study was 97.5%. Conclusion: The common causes of vesico-vaginal fistula in this study were total abdominal hysterectomy and obstetric causes. The success rate was high, yet the attempt should be made to prevent this socially distressing condition. Keywords: VVF, Fistula, Vesico-vaginal Repair.